2014
DOI: 10.1371/journal.pone.0095187
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Adjuvant Activity of IL-2 Presenting Spores of Bacillus subtilis in a Murine Model of Helicobacter pylori Vaccination

Abstract: The endospores of Bacillus subtilis are now widely used as a platform for presentation of heterologous proteins and due to their safety record and high resistance to harsh environmental conditions can be considered as potential vehicles for oral vaccination. In this research we show that recombinant B. subtilis spores presenting a fragment of the Helicobacter acinonychis UreB protein and expressing the ureB gene under vegetative promoter elicit a strong cellular immune response in orally immunized mice when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 47 publications
0
29
1
Order By: Relevance
“…To check how the choice of anchoring protein influences interaction of the recombinant spores with the immune system, we performed mucosal immunization of mice with all variants of the FliD-presenting spores. Since results of our previous research indicated that the recombinant spores did not elicit immune response in mice upon oral immunization without the use of appropriate adjuvants (Hinc et al, 2014;Stasiłojć et al, 2015), we decided to administrate spores by the intranasal route, which was shown to be compatible with such antigen delivery systems (Huang et al, 2010;. We were not able to detect a statistically significant increase in levels of FliD-specific antibodies in sera, lungs or gastrointestinal tracts of immunized animals (data not shown).…”
Section: Immune Response To Recombinant Sporesmentioning
confidence: 91%
See 3 more Smart Citations
“…To check how the choice of anchoring protein influences interaction of the recombinant spores with the immune system, we performed mucosal immunization of mice with all variants of the FliD-presenting spores. Since results of our previous research indicated that the recombinant spores did not elicit immune response in mice upon oral immunization without the use of appropriate adjuvants (Hinc et al, 2014;Stasiłojć et al, 2015), we decided to administrate spores by the intranasal route, which was shown to be compatible with such antigen delivery systems (Huang et al, 2010;. We were not able to detect a statistically significant increase in levels of FliD-specific antibodies in sera, lungs or gastrointestinal tracts of immunized animals (data not shown).…”
Section: Immune Response To Recombinant Sporesmentioning
confidence: 91%
“…(Negri et al, 2013) BAN02 amyE::cotC-fliD (Negri et al, 2013) BAN03 amyE::cotG-fliD (Negri et al, 2013) BAN04 amyE::cotZ-fliD (Negri et al, 2013) Indirect ELISA for detection of antigen-specific antibodies. FliD-specific antibodies in saponin extracts of gastrointestinal tracts or lungs, and sera of the immunized animals were detected as previously described (Hinc et al, 2014). Briefly, plates were coated with 100 ml per well of the specific antigen (2 mg/ml in carbonate/bicarbonate buffer) and left at room temperature overnight.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Major efforts have been devoted to the development of new mucosal vaccination strategies based on adjuvants able to induce sIgA or on novel delivery systems based on synthetic nanoparticles, viral particles, microbial cells or bacterial spores [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%